MENINGKATKAN TRANSPARANSI: MENGURAI FAKTOR-FAKTOR RISIKO JANGKA PENDEK DALAM VOLUNTARY DISCLOSURE - Shafira Nurrahmawati; Shinta Permata Sari (JURNAL ILMIAH EDUNOMIKA, 2024)
Voluntary disclosure is an important topic in Indonesia because of the high level of urgency in increasing transparency. This disclosure is needed to consider future risks that could affect company performance, especially short-term risks. Companies need to take short-term risks in order to deal with uncertainty and persist longer. This research aims to determine the influence of Litigation Risk, Liquidity, and Firm Performance regarding Voluntary Disclosure. This research is a type of quantitative research with using secondary data, namely Annual Reports from property and real estate companies listed on the Indonesia Stock Exchange. The sampling technique used is purposive sampling. The total sample is 18 property and real estate companies during the 2019-2022 period. The regression data analysis method used to test hypothesis. The results of this research show that litigation risk and liquidity have an influence on voluntary disclosure, and firm performance has no influence on voluntary disclosure.